Depletion of macrophages with clodronate liposomes partially attenuates renal fibrosis on AKI–CKD transition. Issue 1 (31st December 2023) - Hu, Zhizhi; Zhan, Juan; Pei, Guangchang; Zeng, Rui
Abstract: Clodronate liposomes are bisphosphonates encapsulated by liposomes that are known to induce macrophage depletion in vivo . In a previous study, clodronate liposomes improved renal ischemia/reperfusion (I/R) injury in mice, which may be due to effects on macrophage phenotypes. However, how inflammatory cytokines secretion participates is unknown. In this study, we investigated the effect of macrophages in the I/R kidney by depleting macrophages with clodronate liposomes and changing inflammatory cytokines. C57BL/6 mice underwent I/R injury with or without clodronate liposomes administration on Days 5 and 15. Tubular injury, collagen deposition, and fibrosis were detected and analyzed by histological staining, immunocytochemistry (IHC), flow cytometry (FACS), and reverse transcription–polymerase chain reaction (RT–PCR). Inflammatory cytokines were detected and analyzed by Western blotting and RT–PCR. We found that clodronate liposomes alleviated renal fibrosis and tissue damage on both Days 5 and 15. KIM-1, IL-10, and TGF-β were reduced significantly in the clodronate liposomes treatment group. However, TNF-α was not different between the clodronate liposomes treatment group and the phosphate-buffered saline treatment group on either Day 5 or Day 15. Thus, clodronate liposomes can alleviate renal fibrosis and tissue damage and reduce the inflammatory cytokines IL-10 and TGF-β, suggesting that clodronate liposomes alleviate renal fibrosis may because of M1/M2 polarization.